Analysis on Resources and Organizational Culture as Sustainable Competitive Advantages in a Printed Newspaper Company in Semarang - Agata Asri Wijayaningsih; Berta Bekti Retnawati; Thomas Indrajaya (Journal of Management and Business Environment (JMBE), 2023)
Competition in printed media business is getting severe in the digital era due to the growing number of online media. Online media presents more varied news in faster ways for the public. The covid-19 pandemic exacerbates the condition as a lot of hotels, government institutions, banks, and private companies stop subscribing printed newspaper. The research aims to analyze whether resources and organizational culture of a printed newspaper company in Semarang imply sustainable competitive advantages. This research implemented qualitative method which was by interviewing three managers and employees of four departments to obtain data. The VRIO analysis was used to analyze the data. The results show that not all company’s resources imply sustainable competitive advantages; only human resources, organizational structure, and market do so. The financial and physical resources possess temporary competitive advantages.  In terms of organizational culture, only kinship implies sustainable competitive advantage. Disciplinary and honesty have competitive parities and identity and policy have temporary competitive advantages